PENGARUH PROFITABILITAS, LEVERAGE, UMUR PERUSAHAAN, RISIKO BISNIS DAN GOOD CORPORATE TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2020 - Akbar Hidayat Rahmad; Efni Yulia; Rahmayanti Elvi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Profitabilty, Leverage, Firm Age, Bussiness Risk, and Good Corporate Governance on Bond Rating. The population in this study involved all manufacturing companies officially listed on the Indonesia Stock Exchange for the period of 2015-2020 totalling 181 companies. A total of 10 samples were obtained using purposive sampling method. The data were analyzed using logostic regression. The results showed that Profitabilty has a significant and positive effect on Bond Rating, Leverage has a significant and negative effect on Bond Rating, Firm Age has no significant effect on Bond Rating, Bussiness Risk has a significant and negative effect on Bond Rating, Good Corporate Governance has no significant effect on Bond Rating.Keywords: Profitabilty, Leverage, Firm Age, Bussiness Risk, Good Corporate Governance, Bond Rating